2018
DOI: 10.1038/s41467-018-05092-w
|View full text |Cite
|
Sign up to set email alerts
|

Widespread anti-CRISPR proteins in virulent bacteriophages inhibit a range of Cas9 proteins

Abstract: CRISPR-Cas systems are bacterial anti-viral systems, and bacterial viruses (bacteriophages, phages) can carry anti-CRISPR (Acr) proteins to evade that immunity. Acrs can also fine-tune the activity of CRISPR-based genome-editing tools. While Acrs are prevalent in phages capable of lying dormant in a CRISPR-carrying host, their orthologs have been observed only infrequently in virulent phages. Here we identify AcrIIA6, an Acr encoded in 33% of virulent Streptococcus thermophilus phage genomes. The X-ray structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
150
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(162 citation statements)
references
References 62 publications
3
150
2
7
Order By: Relevance
“…We next tested three known Acrs for their ability to inhibit SauCas9-mediated genome editing in mammalian cells, including the robust SpyCas9 inhibitor AcrIIA4 (10), the broadspectrum type II-A Cas9 inhibitor AcrIIA5 (12) and the species-specific Streptococcus thermophilus Cas9 inhibitor AcrIIA6 (12). While AcrIIA4 prevented genome editing by SpyCas9 as expected (10), we found that it had no effect against SauCas9 (Fig.…”
Section: Inhibition Of Saucas9-mediated Genome Editing In Human Cellsmentioning
confidence: 59%
See 1 more Smart Citation
“…We next tested three known Acrs for their ability to inhibit SauCas9-mediated genome editing in mammalian cells, including the robust SpyCas9 inhibitor AcrIIA4 (10), the broadspectrum type II-A Cas9 inhibitor AcrIIA5 (12) and the species-specific Streptococcus thermophilus Cas9 inhibitor AcrIIA6 (12). While AcrIIA4 prevented genome editing by SpyCas9 as expected (10), we found that it had no effect against SauCas9 (Fig.…”
Section: Inhibition Of Saucas9-mediated Genome Editing In Human Cellsmentioning
confidence: 59%
“…However, some MGEs, particularly phages, have evolved anti-CRISPRs (Acrs), peptide inhibitors of Cas proteins that block CRISPR defense systems (2,3). Acrs have been discovered to inhibit distinct CRISPR systems, including type I (4)(5)(6)(7)(8), type II (9)(10)(11)(12)(13)(14)(15)(16), type III (17,18), and type V (7,19). Strategies for identifying new Acrs include testing genes of unknown function that are proximal to anti-CRISPR associated (aca) genes (5-7, 9, 15) and screening genes in organisms with self-targeting CRISPR systems (7,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…While characterizing the interplay between St1Cas9 and diverse Acr families isolated from virulent phages infecting S. thermophilus 31 , we were surprised by the substantial levels of editing achieved in human cells 33 . This observation contrasts with early reports indicating that this ortholog was mildly active 7,34 .…”
Section: Identification Of An Sgrna Architecture Directing Robust Dnamentioning
confidence: 98%
“…A number of Acrs have been identified for type I [23,[25][26][27][28], type II [29][30][31][32] and type V [28,33] CRISPR-Cas systems. Acrs can be adapted to regulate CRISPR-Cas activities in bacteria [34], yeast [35] and mammalian cells [29,31,34,[36][37][38]. Biosensor [39] and synthetic circuits [40] can be devised based on Acr-coupled CRISPR-Cas systems.…”
Section: Inhibition Off-target Activitymentioning
confidence: 99%